Bionomics, behaviour and monitoring of the vine snoutbeetle, Phlyctinus callosus Boh., in deciduous fruit orchards, with proposals for an improved control strategy - Barnes, Brian Nigel (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D. Agric.) -- University of Stellenbosch, 1987.